Manage your time : how to work more effectively. (Steps to success (London, England), 2006)
So much work, so little time ... Life at work has never been busier, and it's easy to feel swamped by endless 'to-do' lists, half-written emails, and a constantly-ringing phone. If you want to take back control of your desk, prioritise your work and create more time to enjoy yourself, Manage your time is for you. Now fully revised and updated with a self-assessment quiz and step-by-step advice, this book will help you to avoid information overload, know when to throw things away, learn how to delegate, and get back on top of your inbox. If you want to take back control of your desk, prioritis.